Political theory and the European constitution - Dobson, Lynn; Føllesdal, Andreas (Routledge/ECPR studies in European political science ;, 2004)
This timely volume provides one of the first critical assessments of the draft Constitution (released by the Convention on the future of Europe) from the vantage point of political theory.